2015
DOI: 10.1117/1.jei.24.3.033021
|View full text |Cite
|
Sign up to set email alerts
|

Robust and efficient anomaly detection using heterogeneous representations

Abstract: Various approaches have been proposed for video anomaly detection. Yet these approaches typically suffer from one or more limitations: they often characterize the pattern using its internal information, but ignore its external relationship which is important for local anomaly detection. Moreover, the high-dimensionality and the lack of robustness of pattern representation may lead to problems, including overfitting, increased computational cost and memory requirements, and high false alarm rate. We propose a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Then, the volume is further divided into a set of cuboids with a size of 4 × 4 × 5. We extract the slow features proposed in our previous works [34] from each cuboid as the regional feature, which is robust and discriminative. We construct a 2D HOCG descriptor for each event, i.e., the spatial direction range is quantized into 8 directions with each direction being 45°.…”
Section: Ucsd Dataset 411 Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the volume is further divided into a set of cuboids with a size of 4 × 4 × 5. We extract the slow features proposed in our previous works [34] from each cuboid as the regional feature, which is robust and discriminative. We construct a 2D HOCG descriptor for each event, i.e., the spatial direction range is quantized into 8 directions with each direction being 45°.…”
Section: Ucsd Dataset 411 Resultsmentioning
confidence: 99%
“…We utilize four types of Fig . 7 Examples of detection results for global abnormal event detection from the UNM dataset regional features, i.e., the gray value, 3D gradient, GCM [34], and slow features (SF) [43] descriptors. The comparisons demonstrate that after constructing the HORG descriptors, not only the performance of AED is improved but also the dimensionality is also reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…images or videos) is important to enable a good classification performance for different types of anomalies. In an attempt to classify pattern representation approaches, Hu et al [15] suggested that the methods for representing patterns can be grouped into four main categories: trajectory-based, spatio-temporal-interest-point-based, foreground-blob-based and volume-based. However, methods that can be grouped into one or more categories are frequently observed in the literature and, usually, they have in common the use of hand-crafted features.…”
Section: B Pattern Representationmentioning
confidence: 99%